(untitled) (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
Globalization has accelerated the penetration of secular knowledge frameworks into Muslim-majority societies, intensifying a longstanding crisis of bifurcated education that separates Islamic sciences from modern disciplines. This study examines the concept of nilainisasi ilmu conceptualized as Islamization of Knowledge in line with al-Faruqi’s tawhidic epistemology as a strategic response to this crisis, with specific focus on its operationalization within Indonesian Islamic higher education. Employing a qualitative library research design, this study draws on 50 Scopus-indexed sources to synthesize theoretical frameworks across Islamic epistemology, character education, curriculum integration, and digital pedagogy. Three core findings emerge: (1) the Islamization of Knowledge framework provides a robust epistemological scaffold for integrating Islamic values across all academic disciplines; (2) value internalization operates through cognitive, affective, and psychomotor dimensions simultaneously and requires educator exemplarity as its essential pedagogical condition; and (3) the integration of Islamic values into modern learning enhances students’ moral identity and resilience in the face of globalization’s cultural pressures. The study contributes a synthesized Integrative-Islamic Pedagogy Model (IIPM) and proposes a research agenda for empirical implementation studies in Indonesian UIN contexts